2019
DOI: 10.3390/horticulturae5040072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Composition and Lettuce Cultivar on Crop Production in Hydroponic Culture

Abstract: A greenhouse research study was conducted at Eastern New Mexico University, Portales, NM, USA, in 2019 to examine the effects of different nutrient solutions on the growth and weight of two lettuce cultivars grown in a floating hydroponic system. Two lettuce cultivars, Buttercrunch and Black Seeded Simpson, were subjected to one of four different nutrient concentrations of N, K and Ca at 150, 100, and 150 ppm (N1), 210, 235, and 200 ppm (N2), 250, 300 and 250 ppm (N3), and 300, 350, and 350 ppm (N4), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 28 publications
6
44
0
1
Order By: Relevance
“…The highest yield of lettuce due to high concentrations of nitrate in solution was also verified by Kov ik et al (2014), Galieni et al (2015), Qadir et al (2017) and Sapkota and Liu (2019) who found that there was higher yield with high nitrate levels, and reduction in productivity of plants and slow growth at lower nitrate concentrations. In this context, it is notorious that the increase in nitrogen availability is a major factor in the accumulation of nitrate in plants, reinforcing the point proposed in the literature by Chen et al (2004), Gülser (2005), Turan and Sevimli (2005) and Pôrto et al (2008).…”
Section: Discussionmentioning
confidence: 57%
“…The highest yield of lettuce due to high concentrations of nitrate in solution was also verified by Kov ik et al (2014), Galieni et al (2015), Qadir et al (2017) and Sapkota and Liu (2019) who found that there was higher yield with high nitrate levels, and reduction in productivity of plants and slow growth at lower nitrate concentrations. In this context, it is notorious that the increase in nitrogen availability is a major factor in the accumulation of nitrate in plants, reinforcing the point proposed in the literature by Chen et al (2004), Gülser (2005), Turan and Sevimli (2005) and Pôrto et al (2008).…”
Section: Discussionmentioning
confidence: 57%
“…Observing the data presented in the literature, where vegetables, such as lettuce, which received higher concentrations of nitrogen had leaves with a more intense green color (Rodrigo-García et al, 2019;Sapkota et al, 2019), greater antioxidant activity (Zambrano-Moreno et al, 2015). In addition to having increased concentrations in the contents of phenolics and flavonoids, in organic and hydroponic cultivation systems compared to the conventional system.…”
Section: Resultsmentioning
confidence: 98%
“…1). Whereas soil-based agriculture is more robust, the use of hydroponic systems for the production of vegetables enables faster growth, higher product quality and needs less space (Sapkota, 2019).…”
Section: Introductionmentioning
confidence: 99%